Advances in Digitization of Microphones and Loudspeakers - KULKA, Zbigniew (Archives of Acoustics, 2011)
The development of digital microphones and loudspeakers adds new and interestingpossibilities of their applications in different fields, extended from industrial,medical to consumer audio markets. One of the rapidly growing field of applicationsis mobile multimedia, such as mobile phones, digital cameras, laptop and desktopPCs, etc. The advances have also been made in digital audio, particularly in directdigital transduction, so it is now possible to create the all-digital audio recordingand reproduction chains potentially having several advantages over existing analogsystems.